2015
DOI: 10.1016/j.cell.2015.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Robust Anti-viral Immunity Requires Multiple Distinct T Cell-Dendritic Cell Interactions

Abstract: Summary Host defense against viruses and intracellular parasites depends on effector CD8+ T cells whose optimal clonal expansion, differentiation, and memory properties require signals from CD4+ T cells. Here we addressed the role of dendritic cell (DC) subsets in initial activation of the two T cell types and their co-operation. Surprisingly, initial priming of CD4+ and CD8+ T cells was spatially segregated within the lymph node and occurred on different DC with temporally distinct patterns of antigen-present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

19
307
2
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 275 publications
(332 citation statements)
references
References 48 publications
19
307
2
4
Order By: Relevance
“…In vivo, DC maturation and migration following virus activation are complex and dynamic processes leading to CD4 and CD8 T-cell priming. Recent reports have revealed that for different viruses, infection and DC migration to lymph nodes result in distinct spatially and temporally defined interactions between CD4 and CD8 T cells and multiple subsets of DCs (67,68). The factors that influence these distinct DC interactions with T-cell subsets have not been fully established for Ad infections.…”
Section: Discussionmentioning
confidence: 99%
“…In vivo, DC maturation and migration following virus activation are complex and dynamic processes leading to CD4 and CD8 T-cell priming. Recent reports have revealed that for different viruses, infection and DC migration to lymph nodes result in distinct spatially and temporally defined interactions between CD4 and CD8 T cells and multiple subsets of DCs (67,68). The factors that influence these distinct DC interactions with T-cell subsets have not been fully established for Ad infections.…”
Section: Discussionmentioning
confidence: 99%
“…We here make use of However, they next contacted the same XCR1 þ DCs. This second priming event promoted memory precursor formation and recall capacity of CD8 þ T cells and thus proved to be the platform for delivery of CD4 þ T-cell help (31).…”
Section: Discussionmentioning
confidence: 99%
“…During the revision of this paper, the spatiotemporal characterization of antigen-specific CD4 + T cells and CD8 + T cells in the SDLNs was reported in HSV-1 or vaccinia virus infection (25,26). Although the location and/or timing of initial activation of CD4…”
Section: Discussionmentioning
confidence: 99%
“…It will be needed to investigate whether Xcr1-expressing LN-resident DCs sample antigen from the subcapsular sinus and migrate to the T-cell zone for interacting with CD8 + T cells. More importantly, future studies should perform similar imaging analyses with the Xcr1 KikGR/+ mouse strain during different types of immune responses, because capabilities of the migratory and resident DC subsets to interact with CD8 + T cells are likely to be affected by the types of vaccines and microbes (17,25,26,28).…”
Section: Discussionmentioning
confidence: 99%